Digital Play-Based Pedagogy in Early Childhood Education: A Quasi-Experimental Study of Preschool Cognitive Development - Suryansah; Ari Saputra; Lalu Ibrohim Burhan (PT. LIB Research Cendekia, 2026)
This study examines the influence of play-based digital pedagogy on the cognitive development of early childhood learners in urban PAUD (early childhood education) settings. The rapid integration of digital technologies into education has created new opportunities to develop interactive, learner-centered learning environments. However, empirical research examining how digital pedagogy can be effectively integrated with play-based learning in early childhood education remains limited. This study employed a quasi-experimental research design with a pretest–posttest design to analyze changes in children’s cognitive development following the implementation of a structured, digital, play-based learning intervention. The participants consisted of early childhood learners aged 4–6 years enrolled in urban PAUD institutions. The intervention was conducted over six weeks, integrating digital storytelling, educational game-based learning, puzzle-solving activities, and guided digital exploration within play-based classroom practices. Data were collected using developmental observation checklists and cognitive task assessments that measured symbolic thinking, memory, problem-solving skills, logical classification, and early reasoning. The results indicate a statistically significant improvement in children's cognitive development following the intervention, with notable gains in symbolic reasoning and problem-solving abilities. These findings suggest that digital technologies, when implemented through developmentally appropriate play-based pedagogical strategies, can effectively stimulate cognitive engagement and support early learning processes. The study contributes to the development of an integrative pedagogical model combining digital pedagogy and play-based learning, grounded in Constructivist Learning Theory and Play-Based Learning Theory. It provides empirical evidence for designing innovative, developmentally appropriate digital learning environments in early childhood education.